The impact of extracurricular activities on the fostering of learners' research skills - Rizayeva, Luiza; Kolumbayeva, Sholpan; Umirbekova, Akerke; Zhumabayeva, Zhazira; Yermekbaev, Mukhtar (Journal of Education and e-Learning Research, 2025)
This study examines students' research skills and how extracurricular activities influence the fostering of students' research skills. A mixed-methods approach was used before and after the test. The experiment included 160 participants. The study revealed that research skills were developed formally among the learners through extracurricular activities. The author created and implemented an extracurricular activity programme in the context of experimental manipulation to help the students improve their research skills. A set of measures was carried out to develop research skills through extracurricular activities to support and encourage the students' research search. This study found that extracurricular activities have an impact on students' development of research skills by providing them access to new perspectives and scientific knowledge in the field of problem-solving research, as well as by applying that knowledge in practical settings to support research skills in extracurricular activities.